The Role of Digital Competencies as a Mediating Variable in the Relationship between Organizational Agility and Achieving Institutional Excellence in Secondary Schools in the Southern Governorates - Abu Borhom, Mohammed Ibrahim (Journal of Educational and Psychological Sciences, 2023)
This study aimed at identifying the degree of availability of organizational agility and the reality of digital competencies, as well as identifying the nature and direction of the relationship between organizational agility and institutional excellence, as well as revealing the intermediate role of digital competencies in the relationship between organizational agility and institutional excellence.to achieve the objectives of the study, the researcher built a tool for the study, which was a questionnaire and the sample consisted of (359)of teachers of secondary schools in the southern governorates, The study reached a number of results, the most important of which are: Organizational Agility, Institutional Excellence, and Digital Competencies are highly available. there is a statistically significant effect of the availability of organizational agility on achieve institutional excellence by (54.2%). there is a statistically significant effect of the availability of organizational agility on achieve digital competencies by (60.1%). there is a statistically significant effect of the availability of digital competencies on achieve institutional excellenceby (47.4%). Moreover, digital competencies played a partial mediation role in the relationship between organizational agility and institutional excellence. The study gives a number of recommendations, the most important of which are: the need to pay attention to the, the digital competencies and the work of courses to increase the technological digital of to keep pace with the changes of the times, strengthening the role of innovation, solving problems and providing solutions to various educational fields, organizing workshops to discuss mechanisms to in exploiting the available resources and opportunities besides exploring new opportunities.